PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERBANKAN INDONESIA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Mohammad Arswenda Putra Atmawiaji; Maslichah Maslichah; Abdul Wahid Mahsuni (Universitas Islam Malang, 2022)
The purpose of this study was to determine the effect of Good Corporate Governance on the Financial Performance of Indonesian Banks Listed on the IDX. The population used is all banks listed on the IDX for the 2018-2020 period. The sampling technique was carried out by purposive sampling method. The sample of this research is 25 companies. Data analysis was performed using multiple linear regression method. The results of this study indicate that partially the board of directors and institutional ownership have a significant positive effect on ROA. Meanwhile, the board of commissioners, independent commissioners and audit committee have no effect on ROA.Keywords: Board of Commissioner, Independent Commissioner, Board of Director, Audit Committee, Return On Assets.